(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
Vitiligo represents a complex autoimmune dermatosis characterized by progressive melanocyte destruction mediated through cytotoxic T-lymphocyte activation, autoantibody production, and dysregulated cytokine networks. This investigation examined immunological profiles in 127 vitiligo patients, revealing significantly elevated anti-melanocyte antibodies (78.3%), altered T-cell subsets, and pro-inflammatory cytokine dominance, collectively elucidating the multifactorial autoimmune pathogenesis underlying depigmentation.